A multilinear interaction model: algorithms for Kalai-Smorodinsky solution - Donato, Alessia (Journal of Mathematical Economics and Finance; Vol 3 No 1 (2017): JMEF Volume III, Issue 1(4), Summer 2017DO - 10.14505//jmef.v3.1(4).03, 2017)
We implement Matlab algorithms for the construction and representation of the payoff space in a certain applicable game models, in 2 and 3 dimensions. More- over our algorithms can find the Kalai-Smorodinsky solutions in the same game with some interfering elements. We write down the intersection of the critical zone and the Kalai-Smorodinsky straight-line for finding the compromise solution. We propose a software for the determination of the graphs. In the Appendix we solve the problem in closed form for the 2 and 3 dimensional case and numerical ly for n = 7 .